2013
DOI: 10.1161/circoutcomes.111.000069
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient-Reported Outcomes and Preferences for Same-Day Discharge After Percutaneous Coronary Intervention

Abstract: Background-Same-day discharge after percutaneous coronary intervention (PCI) may be safe for some patients. Few data are available on patient-reported outcomes and preferences for same-day discharge after PCI. Methods and Results-Between March 2008 and March 2010, a total of 298 patients undergoing elective PCI via femoral access at 2 medical centers (Mount Sinai Hospital, New York, NY, and Baylor Medical Center, Dallas, TX) were randomized to same-day (n=150) or next-day (n=148) discharge. The primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 31 publications
1
38
0
1
Order By: Relevance
“…However, there was considerable disagreement among patients about the desirable length of stay: while a procedure performed in day‐care was among the most preferred, confirming the results of previous studies , equal numbers of patients perceived an overnight stay after the procedure as either most desirable or least desirable. We can only hypothesize that elderly patients might prefer the overnight stay, as this patient group is known to more often have difficulty in coping with postprocedural stress and lack of adequate help at home .…”
Section: Discussionmentioning
confidence: 99%
“…However, there was considerable disagreement among patients about the desirable length of stay: while a procedure performed in day‐care was among the most preferred, confirming the results of previous studies , equal numbers of patients perceived an overnight stay after the procedure as either most desirable or least desirable. We can only hypothesize that elderly patients might prefer the overnight stay, as this patient group is known to more often have difficulty in coping with postprocedural stress and lack of adequate help at home .…”
Section: Discussionmentioning
confidence: 99%
“…However, what defines “carefully selected” elective PCI patients has been inconsistently applied, if defined at all 2, 3, 4, 5, 6, 7, 8, 9. Some studies have cautiously explored the feasibility of SDD beyond the low‐risk population,7, 10, 11, 12, 13, 14 but they were evaluated in selected patients or required protocols or checklists.…”
mentioning
confidence: 99%
“…In this era of increasing focus on rising healthcare expenditure, same‐day discharge is associated with reduced costs and greater efficiency. Furthermore, a shorter length of stay after PCI is preferred by the majority of patients . Despite these apparent benefits, the appropriate length of stay after elective PCI remains poorly defined in clinical guidelines and our survey found that routine same‐day discharge is performed by a minority of responding cardiologists.…”
Section: Discussionmentioning
confidence: 84%